2017
DOI: 10.1107/s2052252517010685
|View full text |Cite
|
Sign up to set email alerts
|

Charge-transport properties of 4-(1,2,2-triphenylvinyl)aniline salicylaldehyde hydrazone: tight-packing induced molecular `hardening'

Abstract: Based on first-principles calculations, the relationship between molecular packing and charge-transport parameters has been investigated and analysed in detail. It is found that the crystal packing forces in the flexible organic molecule 4-(1,2,2-triphenylvinyl)aniline salicylaldehyde hydrazone (A) can apparently overcome the dynamic intramolecular rotations and the intramolecular steric repulsion, effectively enhancing the molecular rigidity and decreasing the internal reorganization energy. The conducting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…to the number of carbon atoms in the tail, to which the steric crowding contributes significantly. Furthermore, the observation may be attributed to the presence of bulky long alkoxy chains 48,49 present in M4, as compared with the other two systems (M2 and M3). This physically hinders the electron movement, thereby causing less movement across the depletion layer and rendering a higher drain current output, both of which enhance the sensitivity.…”
Section: Gas Sensing Mechanismmentioning
confidence: 87%
See 1 more Smart Citation
“…to the number of carbon atoms in the tail, to which the steric crowding contributes significantly. Furthermore, the observation may be attributed to the presence of bulky long alkoxy chains 48,49 present in M4, as compared with the other two systems (M2 and M3). This physically hinders the electron movement, thereby causing less movement across the depletion layer and rendering a higher drain current output, both of which enhance the sensitivity.…”
Section: Gas Sensing Mechanismmentioning
confidence: 87%
“…M4 has a higher surface charge/electron density (observed from KPFM), demonstrated by its higher drain current, which arises due to the ineffective recombination of holes and electrons. 47,48 This generally occurs when the electron does not effectively penetrate the depletion layer and enter the M1 layer. This observation can be ascribed Fig.…”
Section: Gas Sensing Mechanismmentioning
confidence: 99%
“…In this work, we selected the adiabatic potential-energy surface method for the evaluation of the reorganization energy. Our previous studies showed that the potential-energy surface method is suitable for both flexible and rigid molecules; in comparison, the normal-mode analysis method is more appropriate for rigid molecules due to the large deviation of the lattice vibration from the harmonic oscillator model for the flexible molecules (Ma, Liu & Huang, 2017;Ma, Chai, Chen & Huang, 2017).…”
Section: Organization Energy Ionization Potential and Electronic Affmentioning
confidence: 99%
“…It is well known that noncovalent interactions, such as π-π stacking, cation-π*/anion-π* and hydrogen bonding, play important roles in various fields such as structural biology, materials science, supramolecular chemistry, and so on. [1][2][3][4][5][6][7][8] Particularly, the hydrogen bonding interactions are crucial to maintain the stability of life-related biomacromolecules like RNA and DNA, also they have significant effects on the structures as well as the properties of materials. [9][10][11][12][13] It cannot be denied that various chemical reactions occur involved in hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%